2013
DOI: 10.3390/ijms14058787
|View full text |Cite
|
Sign up to set email alerts
|

The Cloning and Characterization of the Enolase2 Gene of Gekko japonicus and Its Polyclonal Antibody Preparation

Abstract: The enolase2 gene is usually expressed in mature neurons and also named neuron specific enolase (NSE). In the present study, we first obtained the NSE gene cDNA sequence by using the RACE method based on the expressed sequence tag (EST) fragment from the cDNA library of Gekko japonicus and identified one transcript of about 2.2 kb in central nervous system of Gekko japonicus by Northern blotting. The open reading frame of NSE is 1305 bp, which encodes a 435 amino-acid protein. We further investigated the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…All experimental protocols applied to the animals were approved by the Laboratory Animal Care and Use Committee of our medical school. Animal models of spinal cord injury were established using procedures described previously [ 11 ]. Briefly, rats were anesthetized with 1% pentobarbital sodium, and a laminectomy was applied at the T9 to T10 spinal segment level.…”
Section: Methodsmentioning
confidence: 99%
“…All experimental protocols applied to the animals were approved by the Laboratory Animal Care and Use Committee of our medical school. Animal models of spinal cord injury were established using procedures described previously [ 11 ]. Briefly, rats were anesthetized with 1% pentobarbital sodium, and a laminectomy was applied at the T9 to T10 spinal segment level.…”
Section: Methodsmentioning
confidence: 99%
“…According to the methods followed in our previous study [ 27 ], total RNA was isolated from cells by using TRIzol reagent (Life Technologies, Grand Island, NY, USA). The first strand cDNA was synthesized using an Omniscript Reverse Transcription Kit (Qiagen, Venlo, Limburg, The Netherlands) in a 20-μL reaction system containing 2 μg total RNA.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the universal control (Ctrl) siRNA and gene-specific c3orf1 siRNA are listed in the Table 4 . Protocols used for siRNA experiments were based on our previous study [ 27 ]. For studies involving siRNA in cultured cells, isolated and dissociated cells were transfected using Lipofectamine2000 (Life Technologies, Grand Island, NY, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the refolding and aggregation speed was sometimes too fast when the recombinant protein refolded, leading to the random aggregation formation of certain protein species by the 2 disulfide bonds. The SDS-PAGE results demonstrated that some recombinant proteins were still present in the loaded liquid flow of the Ni 2+ column, indicating that the affinity of the Ni 2+ column on the recombinant His tag protein did not reach saturation, or that the recombinant protein structure itself limited the affinity of the Ni 2+ column on the His tag (20,21). Based on the above analysis, 500 mmol/l of imidazole was selected to directly elute the Ni 2+ column instead of gradient elution to facilitate subsequent protein purification.…”
Section: Discussionmentioning
confidence: 99%